Kualitas Pengungkapan Corporate Social Responsibility pada Perusahaan Sektor Industri Kesehatan yang Listing Di BEI Tahun 2016-2019 - Kurniawati Kurniawati; Diska Arliena Hafni (BALANCE: Economic, Business, Management and Accounting Journal, 2022)
ABSTRACTThis study aims to identify the quality of corporate social responsibility disclosure in the health industry sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2019. The indicators for assessing the quality of CSR disclosure in this study employed GRI G4 indicators with 91 assessment indicators. This study is quantitative descriptive research with content analysis methods. The sample selection in this study used a purposive sampling method, a sample of 15 companies. Data collection was done by accessing the official website of the IDX and the company's website. This study concluded that the health industry sector companies listed on the IDX in 2016-2019 each year experience an increase in the quality of CSR reporting. The improved quality of CSR disclosure during 2016-2019 reflects the commitment of companies in the healthcare industry that are listed on the IDX is getting higher in implementing CSR. PT Phapros, Tbk. in 2016-2019 that have the highest average QCSR, and the company that has the lowest average QCSR is PT SOHO Global Health, Tbk. Companies that have published annual reports and sustainability reports have a better quality of CSR disclosure than companies in the health industry sector that only publish yearly reports. Keywords                    : CSR Quality Disclosure, Global Reporting Initiative, Health Industry  Correspondence to      : diskaarliena@unisayogya.ac.id ABSTRAKPenelitian ini bertujuan untuk mengidentifikasi kualitas pengungkapan corporate social responsibility pada perusahaan sektor industri kesehatan yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2016-2019. Penilaian kualitas pengungkapan CSR menggunakan GRI G4 dengan jumlah 91 indikator. Penelitian ini adalah penelitian deskriptif kuantitatif dengan metode analisis koten/isi. Penelitian ini menggunakan metode purposive sampling, sampel sejumlah 15 perusahaan. Pengumpulan data dengan mengakses situs resmi BEI dan website perusahaan. Penelitian ini menyimpulkan bahwa perusahaan sektor industri kesehatan yang listing di BEI tahun 2016-2019 setiap tahunnya mengalami kenaikan kualitas pelaporan CSR. Peningkatan kualitas pengungkapan CSR selama tahun 2016-2019 mencerminkan komitmen perusahaan semakin tinggi dalam mengimplementasikan CSR. PT Phapros, Tbk tahun 2016-2019 memiliki nilai rata-rata QCSR tertinggi dan terendah pada PT SOHO Global Health Tbk. Perusahaan yang telah menerbitkan annual report dan sustainability report memiliki kualitas pengungkapan CSR yang lebih baik dibandingkan perusahaan yang hanya menerbitkan annual report. Kata Kunci      : Kualitas Pengungkapan CSR; Global Reporting Initiative; Industri Kesehatan